PERTANGGUNGJAWABAN TERHADAP PELAKU YANG MENJALANKAN BISNIS PROSTITUSI (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 94 K/ PID.SUS/2020) - Arif Prasetyo, Muhammad; Armaini Ry, Agus; Vernando Munthe, Sotar; J. Hutapea, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
To get all their desires instantly, women are willing to work as prostitutes. The research method is normative, sourced from library materials. The legal material is in the form of the Criminal Code, the TPPO Law and Law No. 31 of 2014 concerning Victim and Witness Protection. The results of this research show that victims of prostitution receive legal protection, such as keeping their identities secret, justice, restitution, rehabilitation and legal assistance based on Articles 43 to 54 of Law No. 21 of 2007 concerning TIP. Decision No. 94 K/Pid.Sus/2020 explains that in cases of criminal acts of human trafficking, the defendant was sentenced to prison for 5 (five) years based on Article 2 of Law No. 21 of 2007 concerning TIP, considering the victim's consent to work with the defendant. This thesis is entitled: Accountability for Perpetrators Who Run a Prostitution Business (Study of Supreme Court Decision Number 94 K/Pid.Sus/2020). The formulation of the problem is legal protection for women who are victims of prostitution and the judge's considerations in giving Supreme Court decision number 94 K/Pid.Sus/2020.